2021
DOI: 10.1097/ccm.0000000000004938
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning and Survival in Mechanically Ventilated Patients With Coronavirus Disease 2019–Related Respiratory Failure*

Abstract: OBJECTIVES: Therapies for patients with respiratory failure from coronavirus disease 2019 are urgently needed. Early implementation of prone positioning ventilation improves survival in patients with acute respiratory distress syndrome, but studies examining the effect of proning on survival in patients with coronavirus disease 2019 are lacking. Our objective was to estimate the effect of early proning initiation on survival in patients with coronavirus disease 2019–associated respiratory failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
3
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 32 publications
7
84
3
18
Order By: Relevance
“…In addition, approximately 50% of patients were not placed in PP at Day-1 despite PaO 2 /FiO 2 ratio lower than 150 mmHg. Those ndings are consistent with results of previous studies (11,12). In a recent observational study, Mathews et al reported that 44% of intubated patients a PaO 2 /FiO 2 ratio less than 100 mmHg were not placed in PP during the rst 2 days, and only 30% of patients experienced proning during their ICU stay (11).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, approximately 50% of patients were not placed in PP at Day-1 despite PaO 2 /FiO 2 ratio lower than 150 mmHg. Those ndings are consistent with results of previous studies (11,12). In a recent observational study, Mathews et al reported that 44% of intubated patients a PaO 2 /FiO 2 ratio less than 100 mmHg were not placed in PP during the rst 2 days, and only 30% of patients experienced proning during their ICU stay (11).…”
Section: Discussionsupporting
confidence: 90%
“…Although the percentage of patients receiving invasive mechanical ventilation decreased over time across all age groups, use of noninvasive respiratory support, such as bilevel positive airway pressure, continuous positive airway pressure, and high-flow nasal cannula, increased. Several studies have shown improved outcomes with prone positioning ( 37 ) and use of noninvasive ventilatory support in lieu of invasive mechanical ventilation ( 11 , 15 , 38 ) for patients with acute respiratory failure associated with COVID-19. Decreasing use of invasive mechanical ventilation may have also lessened the need for ICU-level care because other types of respiratory support could be delivered in non-ICU settings ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the percentage of patients receiving invasive mechanical ventilation decreased over time across all age groups, use of non-invasive respiratory support modalities, such as BIPAP, CPAP and HFNC increased over the same time-period. Several studies have shown improved outcomes with prone positioning (31) and use of non-invasive ventilatory support in lieu of invasive mechanical ventilation (11, 16, 32) for patients with COVID-19-associated acute respiratory failure. Decreasing use of invasive mechanical ventilation may have also lessened the need for ICU level care, as other respiratory support modalities could be delivered in non-ICU settings.…”
Section: Discussionmentioning
confidence: 99%